Mesomorphism and Photophysics of Some Metallomesogens Based on Hexasubstituted 2, 2′:6′, 2′′‐Terpyridines. Issue 24 (3rd May 2016) - Kumar, N. S. Saleesh; Shafikov, Marsel Z.; Whitwood, Adrian C.; Donnio, Bertrand; Karadakov, Peter B.; Kozhevnikov, Valery N.; Bruce, Duncan W.
Abstract: The luminescent and mesomorphic properties of a series of metal complexes based on hexacatenar 2, 2′:6′, 2′′‐terpyridines are investigated using experimental methods and density functional theory (DFT). Two types of ligand are examined, namely 5, 5′′‐di(3, 4, 5‐trialkoxyphenyl)terpyridine with or without a fused cyclopentene ring on each pyridine and their complexes were prepared with the following transition metals: Zn II, Co III, Rh III, Ir III, Eu III and Dy III . The exact geometry of some of these complexes was determined by single X‐ray diffraction. All complexes with long alkyl chains were found to be liquid crystalline, which property was induced on complexation. The liquid‐crystalline behaviour of the complexes was studied by polarising optical microscopy and small‐angle X‐ray diffraction. Some of the transition metal complexes (for example, those with Zn II and Ir III ) are luminescent in solution, the solid state and the mesophase; their photophysical properties were studied both experimentally and using DFT methods (M06‐2X and B3LYP). Abstract : Bright ideas : The luminescent and mesomorphic properties of a series of metal complexes based on hexacatenar 2, 2′:6′, 2′′‐terpyridines (see figure) are investigated using experimental methods and density functional theory. The ligands in this study show a remarkable ability to promote liquid crystal behaviour when complexed to a wide range of metals where the liquid crystallinity extends over a very wide temperature range.